The ha-ha : a novel - King, Dave (New York : Little, Brown, and Company, 2005)
Howard Kapostash has not spoken in thirty years. The small repertory of gestures and simple sounds that he uses to communicate leads most people to assume he is disturbed, and no one understands that Howard is still the same man he was before a wartime injury. But when he agrees to help an old girlfriend by opening his home to her nine-year-old son, the presence of this nervous, resourceful boy in his life transforms Howard utterly. He is afforded a rare glimpse of life outside his shell--with all its exuberant joys and crushing sorrows.
Keywords: Vietnam War, -- 1961-1975 -- Veterans -- Fiction; Psychological fiction